Quality initiatives of intermediary institutions - the provision of the Chambers: A status quo survey of initiatives by the Chambers of Industry and Commerce and Chambers of Crafts to support the assurance and development of the quality of company-based training - Helena Sabbagh; Moritz Ansmann (Bundesinstitut für Berufsbildung (BIBB), 2023)
The chambers play a central role in ensuring the quality of in-company training. According to the BBiG, their tasks include organising examinations, advising companies and trainees, and monitoring the implementation of in-company training. In addition to these legally defined tasks, the chambers have expanded their quality assurance services for training companies in recent years in order to support them even better in providing good training. This has resulted in a wide variety of innovative approaches throughout Germany that address the promotion, safeguarding and awarding of in-company training quality. A multi-stage, multi-method approach was used to focus on these 'quality initiatives' so that this overview study offers the first systematic stocktaking of this commitment of intermediate institutions using the example of the Chambers of Crafts and the Chambers of Industry and Commerce. The study was prepared by DEQA-VET as part of the project 'Quality initiatives of intermediary institutions and voluntary certification offers for small and medium-sized training companies in the dual system' (duration 2019 to 2021), which was funded by the EU Erasmus+ programme.
urn:nbn:de:0035-1044-9
Keywords: 370